1999
DOI: 10.1007/s101470050043
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' perspectives on "do-not-resuscitate" (DNR) orders

Abstract: Background. The purpose of this study was to investigate physicians' perspectives on do-not-resuscitate (DNR) orders at Tokai University hospital, where a euthanasia-like accident occurred several years ago. Methods. A "questionnaire on DNR orders" survey was administered to physicians and the anonymous answers were collected 2 weeks later. Results. Answers were received from 150 of the 400 physicians (37.5%) (surveyed from every department), and revealed that more than 90% of the physicians felt that DNRs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…The results also show that there is no significant relationship between physicians’ attitudes toward the DNR order, sex, work experience, and specialty, but there were significant differences between the attitudes of doctors in terms of their education level. In the study of Hosaka et al, 19 >90% of the physicians had a positive attitude toward DNR order. In another study, medical students had significantly more positive attitudes toward DNR order compared to nonmedical students.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The results also show that there is no significant relationship between physicians’ attitudes toward the DNR order, sex, work experience, and specialty, but there were significant differences between the attitudes of doctors in terms of their education level. In the study of Hosaka et al, 19 >90% of the physicians had a positive attitude toward DNR order. In another study, medical students had significantly more positive attitudes toward DNR order compared to nonmedical students.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, 67.8% of the physicians had experience in executing the DNR order. In this context, in the study by Hosaka et al, 19 >60% of doctors participated in the decision-making process about DNR order, and this rate was 100% in the study by Cardoso et al 23 Anther study in Iran on resident and intern physicians showed that only 30% of interns and 40% of residents participated in the issuance and implementation of a DNR order. 2 The difference in the participation in DNR may be attributed to the variety in the target groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…103 Japanese nurses participated in the DNR decision almost half of the time, and one third did not believe such orders should be written without the consent of the patient. 104 Recent studies have also been exploring the differences in attitudes toward DNR decision making between physicians, nurses, and other health care professionals, such as bioethicists. Differences in training and personal religious beliefs have been suggested as responsible for variations in attitudes.…”
Section: Studies Of Health Care Practioner Attitudes Toward Dnr Ordersmentioning
confidence: 99%